Sequence variation in the 18S rRNA gene, a target for PCR-based malaria diagnosis, in Plasmodium ovale from southern Vietnam. - Kawamoto, F (1996)
Field surveys of malaria were performed in southern Vietnam by using an acridine orange staining method for rapid diagnosis and a PCR-based, microtiter plate hybridization method for accurate diagnosis. A total of three patients of Plasmodium ovale infection were detected, but PCR-amplified DNA of the P. ovale isolates from two of the patients did not hybridize with the P. ovale-specific probe. Analysis of the target sequence in the 18S rRNA gene indicated that in the DNA of isolates from both patients three nucleotides in the probe region from the typical P. ovale sequence were different, with deletions of two nucleotides and the substitution of one nucleotide. These results may suggest that in addition to molecular biological methods, careful microscopic examination of stained thin blood films is still required in studies of the prevalence of different malaria species.